2012
DOI: 10.1371/annotation/6a5108f5-50f8-418e-854d-8f3eb94e6fc0
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Evaluation of Candidate Reference Genes for Normalization of Quantitative RT-PCR in Soybean Tissues under Various Abiotic Stress Conditions

Abstract: Quantitative RT-PCR can be a very sensitive and powerful technique for measuring differential gene expression. Changes in gene expression induced by abiotic stresses are complex and multifaceted, which make determining stably expressed genes for data normalization difficult. To identify the most suitable reference genes for abiotic stress studies in soybean, 13 candidate genes collected from literature were evaluated for stability of expression under dehydration, high salinity, cold and ABA (abscisic acid) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
2
8
0
1
Order By: Relevance
“…qRT-PCR was carried out using the TransScript tip green qPCR SuperMix kit, following the manufacturer’s instructions (Transgen). The Glyma.19G147900.1 gene was used as an internal control [55]. Statistical analyses were performed using a t-test, and p < 0.05 and < 0.01 were considered significant and extremely significant differences, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was carried out using the TransScript tip green qPCR SuperMix kit, following the manufacturer’s instructions (Transgen). The Glyma.19G147900.1 gene was used as an internal control [55]. Statistical analyses were performed using a t-test, and p < 0.05 and < 0.01 were considered significant and extremely significant differences, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Under these stresses, increased levels of endogenous ABA can upregulate many stress-related genes in an ABA-dependent manner [37]. Numerous studies have identified and validated RGs in rice [38], maize [39], soybean [40,41], and carrot [42] under abiotic stress. However, there are currently no reports of RGs that are universally and stably expressed under abiotic stress in P. ussuriensis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 60S rRNA was stably expressed among different developmental stages in Panax ginseng [50]. Others include RPL30, which has been used as an RG in roots and shoots of soybean seedlings under cold stress and ABA treatment [40], and RPL2, which is stably expressed under nitrogen, cold, and light stress in tomato [8]. Ribosomal protein genes are also widely used as RGs in animals [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation for reactions, thermal profile and melting curve analysis in RT-qPCR assay (Mastercycler®ep realplex, Eppendorf, Hamburg, Germany) was described in our previous study [97]. Fbox [107] was used as the reference gene for normalization based on the 2 −∆Ct method [108]. LinRegPCR software (version 2020.2, Academic Medical Center, Amsterdam, The Netherlands) was used to calculate the efficiency of PCR reactions.…”
Section: Gene Expression Analysis By Rt-qpcrmentioning
confidence: 99%